TRAINING IN MAKING BISCUIT BASED CHOOSE AS A HEALTHY FOOD SUPPLEMENT TO PREVENT NUTRITIONAL NUTRITION DURING THE COVID-19 PANDEMIC - Sakung, Jamaludin M; Pulukadang, Sri Hastuti Virgianti; Rahmawati, Sitti; Ahmar, Dewi Satria (LPPM Univ. Ibn Khaldun Bogor, 2022)
When the chayote harvest is abundant, the farmer group partners are unable to process all the chayote due to limited production capacity. Partners have tried to make flour products but failed. Therefore, the priority carried out by the proposer with partners is in the flour processing process and continued with the manufacture of biscuits. At the time of abundant harvest, chayote cannot be stored so technology is needed to process chayote that can be stored in the form of healthy food to increase nutritional needs. To increase the utilization of the abundance of chayote, one of them can be done in the process of making flour and processed products. The problem faced by partners is the lack of information obtained by farmer groups about the manufacture of flour and processed chayote which has nutritional value and can be used as a substitute for wheat flour for food products in the form of biscuits. Solutions to solving the problem are carried out through training or workshops and guidance on the manufacture of chayote-based flour and biscuits. Making flour from chayote and processed healthy food based on chayote flour (biscuits) can improve health and prevent malnutrition during the Covid-19 pandemic for the people of the Gumbasa sub-district, especially mothers.